Elevation of the resistance of heat-cured acrylic denture base resin against biofilm-forming Candida albicans by incorporating Amphotericin B or Clotrimazole - Ali Abdul Hussein S. AL-Janabi; Makarem M Abdulkareem (Wolters Kluwer Medknow Publications, 2018)
Aim: The ability of antifungal agents to reduce or eliminate biofilm formation by Candida albicans after incorporating heat-cured acrylic denture base materials was investigated. Materials and Methods: Different concentrations of Amphotericin B (AmB) and Clotrimazole (CT) were incorporated into polymethylmethacrylate (PMMA) specimens (10 mm × 10 mm × 2 mm). C. albicans was stimulated to produce biofilms on the surface of specimens. Biofilm count was determined by crystal violet and transmittance percentage assays. Porosity percentage of PMMA specimens was measured. Results: AmB and CT showed more effective action against C. albicans biofilms at low concentrations (1, 5, and 10 μg/ml). Meanwhile, high concentrations (25 and 50 μg/ml) showed less activity. Porosity percentage was decreased in PMMA containing low concentrations of both antifungal agents. Conclusion: Incorporation of AmB and CT into denture materials has a significant inhibitory effect on the biofilm produced by C. albicans, especially at low concentrations. Decrease in porosity level is another advantage evidenced by incorporating low concentrations of AmB and CT within denture.